A critical analysis of corporate social responsibility as a PR practice in Cyprus and Greece. (2015) - Komodromos, Marcos
There has been a significant increase in corporate social responsibility (CSR) during the last five years in Cyprus and Greece. This paper is aimed at both researchers and public relations (PR) practitioners. The contribution of CSR practice from organisations is regarded as an important topic for Cyprus and Greece, and is a topic that received academic and practice attention and is becoming a mainstream issue for many organisations. This research represents a study of current practice of CSR and an examination of their contribution and the fulfilment of its three pillars - social, economic, and environmental - understanding better the thematic areas of CSR currently taking place in both countries. This research employs a qualitative methodology. Understanding how communication practitioners contribute and practice CSR in Cyprus and Greece can have a positive impact in terms of greater public visibility of organisations that create interest in the different sectors, and leads to greater public scrutiny of these firms.